Comparison of the Four Formulas of Adjusting QT Interval for the Heart Rate in the Middle‐Aged Healthy Turkish Men - Dogan, Abdullah (Ann Noninvasive Electrocardiol, 2005)
Objective: The aim of this study was to evaluate the QT intervals at different rest heart rates in healthy middle‐aged Turkish men and to compare the known four QT adjusting methods for heart rate. Methods and Results: The QT intervals were measured in electrocardiograms of 210 healthy men (mean age = 35–60 years). A curve relating QT intervals and heart rates from 45 to 135 beats/min was constructed for study population. Based on the formula of Bazett, Fridericia, and Framingham, adjusted QT intervals in these range of heart rates were separately estimated. An adjusting nomogram for different heart rates was created using a reference value, which was the measured QT interval at heart rate of 60 beats/min (QT(No)= QT + correcting number). These four QT correction methods were compared with each other. The reference value of QT interval at heart rate of 60 beats/min was 382 ms. The relationship between QT and RR interval was linear (r = 0.66, P < 0.001). Nomogram method corrected QT interval most accurately for all the heart rates compared with other three adjusting methods. At heart rates of 60–100 beats/min, the equation of linear regression was QT = 237 + 0.158 × RR (P < 0.001). Bazett's formula gave the poorest results at all the heart rates. The formulas of Fridericia and Framingham were superior to Bazett's formula; however, they overestimated QT interval at heart rate of 60–110 beats/min (P < 0.01). At lower rates (<60 beats/min), all methods except nomogram method, underestimated QT interval (P = 0.03). Conclusion: Among four QT correction formulas, the nomogram method provides the most accurately adjusted values of QT interval for all the heart rates in healthy men. Bazett's formula fails to adjust the QT interval for all the heart rates.